Dietary intake and physical activity levels of children attending Australian childcare services. Issue 5 (30th August 2017) - Jones, Jannah; Wyse, Rebecca; Wiggers, John; Yoong, Sze L.; Finch, Meghan; Lecathelinais, Christophe; Fielding, Alison; Clinton‐McHarg, Tara; Hollis, Jenna; Seward, Kirsty; Wolfenden, Luke
Abstract : Aim: The primary aim of this study was to describe the dietary intake and physical activity levels of children while attending childcare. Methods: A cross‐sectional study was conducted with 18 centre‐based childcare services in the Hunter region of New South Wales, Australia. Childcare service characteristics were assessed via telephone interview. Child dietary intake and physical activity levels were assessed during a one‐day observation conducted at participating childcare services using previously validated tools. Results: Children consumed a mean of 0.2 serves of vegetables, 0.7 serves of fruit, 1.4 serves of grain (cereal) foods, 0.1 serves of lean meat and poultry, fish, eggs, nuts and seeds and legumes/beans, 0.6 serves of milk, yoghurt, cheese and alternatives, and 0.7 serves of discretionary foods during attendance at childcare. Of all child physical activity counts, 48.6% were classified as 'sedentary', and 22.3% classified as 'very active'. Bivariate analyses indicated that children attending services located in rural areas consumed significantly more serves of vegetables (0.3 serves (SD 0.7) vs 0.1 serves (SD 0.2), P = 0.05). Multivariate analyses indicated that services with large child enrolments had a significantly greater proportion of child counts classified as 'very active' (23.6% of child counts (95% CI 1.6, 29.5) vs 14.9% of child counts (95% CI 9.1, 20.6), P = 0.007). Conclusions: There is considerable scope to improve the diet and activity behaviours of children during attendance at childcare. Future research is needed to identify effective strategies to best support childcare services in implementing policies and practices to improve such behaviours in children.